X‐ray‐induced reduction of a surfactant/polyoxotungstate hybrid compound. (2nd August 2018) - Colusso, Aaron V.; McDonagh, Andrew; Cortie, Michael B.
Abstract : We investigate the spontaneous reduction of a photochromic surfactant/polyoxotungstate hybrid during repeated X‐ray photoelectron spectroscopy (XPS) scans and show how this effect may confound attempts to use soft X‐rays to characterise materials of this nature. The W4f core‐level spectra revealed a progressive increase of W 5+ and W 4+ species at the expense of W 6+ as irradiation time increased. The samples developed a blue colour attributed to the presence of W 4+ and/or W 5+ . The progressive photoreduction is also associated with a shift of the W 6+ peak within the W4f spectrum to lower binding energies. This work highlights the need to consider inadvertent changes in oxidation state during X‐ray photoelectron spectroscopy characterisation of samples containing photoreducible transition metals.